PENGEMBANGAN MEDIA PEMBELAJARAN DESAIN GRAFIS BERBASIS ANDROID MENGGUNAKAN UNITY 3D UNTUK SISWA KELAS X SEMARANG - Novianti, Dewi; Supandi, Supandi; Wijonarko, Wijonarko (Universitas PGRI Semarang, 2022)
Based on the practical experience of teaching in class X SIJA SMK N 7 Semarang, researchers conducted observations and interviews and found several facts, namely the teaching methods used by teachers were still using lecture and dictating methods. The media used is only powerpoint, with the limitations of the media, an interesting learning media is needed to increase students' interest in learning. With these problems, researchers innovate to make JARFIS learning media to learn-based graphic design android. The purpose of this research is to produce JARFIS learning media based on android that is feasible and valid to use, makes it easier for students to learn, makes it easier for teachers to teach. In the process of making this product using research methods Research and Development (RD) with 6 stages: potential and problems, data collection, product design, design validation, design revision and product testing. The development model uses the model ADDIE (analysis, design, development, implementation, and evaluation). JARFIS learning media was created using Unity 3D and Coreldraw X7 to design the display and buttons. Based on the results of tests that have been carried out by two media validators, an average of 92% is obtained with the criteria of